Policies and methods for industrial development - Bryce, Murray D. (New York : McGraw-Hill, 1965)
This is a manual on the preparation and evaluation of industrial projects.
Includes bibliographical references (p. 299-301.)
lje 10/4/17
Loans
Keywords: Economic development; Industrialization